Gatekeeping in health care - Kurt R. Brekke; Robert Nuscheler; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2005)
We study the competitive effects of restricting direct access to secondary care by gatekeeping, focusing on the informational role of general practitioners (GPs). In the secondary care market there are two hospitals choosing quality and specialisation. Patients, who are ex ante uninformed, can consult a GP to receive an (imperfect) diagnosis and obtain information about the secondary care market. We show that hospital competition is amplified by higher GP attendance but dampened by improved diagnosing accuracy. Therefore, compulsory gatekeeping may result in excessive quality competition and too much specialisation, unless the mismatch costs and the diagnosing accuracy are sufficiently high. Second-best price regulation makes direct regulation of GP consultation redundant, but will generally not implement first-best.
Keywords: I18; I11; D82; L13; 330; gatekeeping; imperfect information; quality competition; product differentiation; price regulation; Gesundheitswesen; Gesundheitspolitik; Ärzte; Theorie; Hausarztsystem